Cell type–dependent role of transforming growth factor-β signaling on postnatal neural stem cell proliferation and migration - Kierra Ware; Joshua Peter; Lucas McClain; Yu Luo (Neural Regeneration Research, 2026)
Adult neurogenesis continuously produces new neurons critical for cognitive plasticity in adult rodents. While it is known transforming growth factor-β signaling is important in embryonic neurogenesis, its role in postnatal neurogenesis remains unclear. In this study, to define the precise role of transforming growth factor-β signaling in postnatal neurogenesis at distinct stages of the neurogenic cascade both in vitro and in vivo, we developed two novel inducible and cell type-specific mouse models to specifically silence transforming growth factor-β signaling in neural stem cells in (mGFAPcre-ALK5fl/fl-Ai9) or immature neuroblasts in (DCXcreERT2-ALK5fl/fl-Ai9). Our data showed that exogenous transforming growth factor-β treatment led to inhibition of the proliferation of primary neural stem cells while stimulating their migration. These effects were abolished in activin-like kinase 5 (ALK5) knockout primary neural stem cells. Consistent with this, inhibition of transforming growth factor-β signaling with SB-431542 in wild-type neural stem cells stimulated proliferation while inhibited the migration of neural stem cells. Interestingly, deletion of transforming growth factor-β receptor in neural stem cells in vivo inhibited the migration of postnatal born neurons in mGFAPcre-ALK5fl/fl-Ai9 mice, while abolishment of transforming growth factor-β signaling in immature neuroblasts in DCXcreERT2-ALK5fl/fl-Ai9 mice did not affect the migration of these cells in the hippocampus. In summary, our data supports a dual role of transforming growth factor-β signaling in the proliferation and migration of neural stem cells in vitro. Moreover, our data provides novel insights on cell type–specific-dependent requirements of transforming growth factor-β signaling on neural stem cell proliferation and migration in vivo.